Compensation for Damages Caused by Artificial Intelligence under Indonesian Civil Law - Rai Mantili; Sherly Ayuna Putri; Efa Laela Fakhriah (Faculty of Law, Universitas Pekalongan, 2025)
Artificial intelligence (AI) is a technology that refers to the simulation of human intelligence programmed into electronic devices to think like humans and mimic human actions. The rapid development of AI has sparked debates in the legal field, particularly when errors occur and cause harm to the public. Currently, Indonesian law does not explicitly regulate legal protection for a party who suffers material or immaterial damages due to errors caused by AI. This research aims to contribute to the development of civil law discourses through a normative and descriptive approach. The data used are secondary data, and a qualitative method is used to analyze and present the data descriptively. The research finds that there are no specific regulations governing liability for material or immaterial damages resulting from AI activities. The conclusion drawn is that AI cannot be considered a legal subject and lacks control over its actions and intent. Therefore, the burden of compensation for errors caused by AI falls on the creators and users of AI, as stipulated under Article 1365 of the Civil Code and Article 1367 of the Civil Code, which states that: